Oral therapy for erectile dysfunction: An overview - Soni, M; Patidar, K; Sharma1, D; Soni2, P; Sharma2, D K (Asian Journal of Pharmaceutics (AJP), 2014)
Over the past 20 years, treat ment options for erectile dysfunction (ED) have become more effective and, despite the effectiveness of intracavernous injections, vacuum devices, surgery and other treatments, there has been a trend toward the development of less-invasive modalities. Oral drugs have become the first-line therapeutic option for many men with ED. This review highlights the pathophysiology of ED, oral therapy for ED and new drug targets for the treatment of ED products available in the market for ED.